Fuzzy computing with expressions for evaluating fonts styles on children websites - Mahmud, Murni; Raja Mohd, Noorhazwani; Md. Tap, Abu Osman (IIUM Press, 2011)

(untitled)
Children may have difficulty in understanding liked scale in rating websites. However, they are easily attracted to images and icons. Therefore, in any evaluation with children, use of images and icon can be used instead of numbers. This study proposes to try fuzzy computing with expression as a method for children to evaluate websites. It uses linguistic expressions as a method in the evaluation process. Linguistic expressions are applicable to children where expressions are much likeable by children than numerical scaling (e.g. 1 to 5 rating). Evaluation with linguistic expression is applied during the interviews, questions and answers session with the children. Children websites were chosen for evaluation as a proof of idea that linguistic expression work better for children. Websites are important to children as one of the media for education learning and entertainment; however, children websites in Malaysia seems to be limited. This chapter shades some results from a pilot study as the outcomes of using fuzzy computing with expression with Children. The evaluation focus on fonts styles on the children websites. In addition, it also describes a scenario of children websites development and advancement in Malaysia.